Overview of Research on Chinese MOOCs - Zheng, Qinhua; Chen, Li; Burgos, Daniel (Lecture Notes in Educational Technology, 2020)
MOOCs have been in the spotlight since its debut in China in 2012. Later, MOOC platforms and relevant courses developed by different organizations sprung up like mushrooms. Now MOOCs can be seen in multiple forms in practice and have promoted the development of Chinese educational reform in different levels and to different degrees. The research team investigated MOOCs in China from three aspects, namely, MOOC platforms and courses, colleges and universities, and MOOCs learners (in cooperation with Guokr).
Capítulo del libro "Zheng Q., Chen L., Burgos D. (2018). The Development of MOOCs in China. Lecture Notes in Educational Technology. Springer, Singapore"
Keywords: MOOC platform; MOOC learners; chinese educational reform; relevant courses; weChat platform; Scopus(2); WOS(2)